Pergeseran Perilaku Politik Kiai dan Santri di Pamekasan Madura - Zainuddin Syarif (IAIN Ponorogo, 2016)
Abstract, this research applied qualitative approach, by using field research model. The qualitative approach model that is applied emphasize more on Phenomenological perspective, which is focus on the interpretation and emic meaning analysis in the forms of expressions (empiric) found in the field. While the focus of this research concists of (1) what is the meaning of